Clinical Outcomes of the Use of an Innovative Sharp-Tipped Hemostatic Device - พงศ์วศิน พัชรีภรณ์ (Journal of Health Science of Thailand, 2024)
Most surgeries require the use of an electrical cautery device to stop the bleeding and cut tissue. Electric cautery head sold in hospitals has a large flat tip unsuitable for surgery and stopping bleeding in small or narrow areas, resulting in injury to nearby organs. This research is a quasi-experimental research. The objective was to compare the injury to nearby tissues and organs between a pointed-tip electrocautery and a normal electrocautery. The sample group consisted of patients who received services at the operating room of the Otolaryngology Department, Amnat Charoen Hospital from 1 October 2021 to 30 September 2022, totaling 140 people, who were selected by simple random sampling, divided into an experimental group of 70 people and a control group of 70 people by means of individual matching. The tools used included a form to record injuries to nearby tissues and organs and the use of an electric cautery during surgery. The validity and reliability were checked by 3 experts and the content validity index was 0.89 and 0.85, respectively. Data on injury to nearby tissues and organs were analyzed by comparing the pointed end electric cautery head and the normal electric cautery head. Data were analyzed by using paired t-test to compare the means of the 2 groups. The results of the study revealed that the use of a pointed electric cauterizer caused less injury to nearby tissues and organs during surgery than when using a normal cauterizer (p<0.05). It is an innovation created from observing problems that occur with patients during surgery; and the innovation can prevent problems from damaging nearby tissues and organs and improve the efficiency of nursing practice. It is beneficial and convenient to use and it can also reduce hospital costs.